GEOLOGI SEJARAH DAERAH SUKABUMI-PELABUHAN RATU - -, Syahroel Alam Alif (Bulletin of Scientific Contribution, 2011)
This paper is about the geological history of the area Sukabumi-Pelabuhan Ratu, is an article from the author prepared in 1999, when the author is still active as a staff lecturer at the Faculty of Engineering Geology, Unpad. Historical geology of Sukabumi-Pelabuhan Ratu, interesting to learn, especially the most ancient rocks (Ciletuh Formation) to the youngest rocks. Tectonic framework is also interesting to learn, especially because of the influence of Indo-Australia plates are moving toward the north and subducting the Eurasian plate.